2016
DOI: 10.2486/indhealth.2015-0164
|View full text |Cite
|
Sign up to set email alerts
|

Effect of management training in organizational justice: a randomized controlled trial

Abstract: Organizational justice (OJ) influences the well-being of employees of organizations. We conducted a randomized controlled trial to examine whether or not brief management training increases OJ for subordinates. Study participants were managers and subordinates working in the private manufacturing sector. Randomization at the departmental level generated an intervention group of 23 departments (93 managers and 248 subordinates) and a control group of 23 departments (91 managers and 314 subordinates). Managers i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…Thereby we see a potential in future research aiming at affecting these important outcomes through improvements of organizational justice climate. Even though climatic factors may be complicated to address in interventions, a way forward seems to be through training of managers to promote organizational justice for their subordinates (Nakamura et al 2016 ). Though, worth noticing is that this is just one aspect for finding solutions of a complex problem.…”
Section: Discussionmentioning
confidence: 99%
“…Thereby we see a potential in future research aiming at affecting these important outcomes through improvements of organizational justice climate. Even though climatic factors may be complicated to address in interventions, a way forward seems to be through training of managers to promote organizational justice for their subordinates (Nakamura et al 2016 ). Though, worth noticing is that this is just one aspect for finding solutions of a complex problem.…”
Section: Discussionmentioning
confidence: 99%
“…There are also implications for the employer, in relation to their processes for supporting the employee with chronic pain to offset or minimise the potential negative repercussions of weak organisational justice beliefs in relation to, for example, job satisfaction, commitment and work performance (Van Dijke and De Cremer, 2016). Evidence suggests training employers in organisational justice techniques can improve perceptions of fairness and occupational functioning among employees (Nakamura et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, even when the changes were favourable, frequent changes in a relatively short period cause the burden of readjustment and might increase the risk for SPD. Several studies have revealed that OJ is modifiable by intervention 14–17. However, the effect of long-term continuous change has not been examined.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have revealed that favourable changes in OJ have desirable consequences on health outcomes and vice versa,10–12 that optimal OJ promotes recovery from stress reactions such as sleep disorders,12 13 and that OJ can be modified by intervention 14–17. Nevertheless, to our knowledge, the relationship between OIJ and mental disorders has not yet been studied with regard to the effects of exposure duration, frequency of change in OIJ exposure and the OIJ-free period after the disappearance of exposure.…”
Section: Introductionmentioning
confidence: 99%